PENGEMBANGAN KAPASITAS TEKNOLOGI INFORMASI PEGAWAI KANWIL DJP JAKARTA SELATAN II MELALUI PELATIHAN MS. EXCEL TINGKAT DASAR - Noni Juliasari; Rusdah; Dewi Kusumaningsih; Ratna Ujiandari (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
AbstractThe achievement of company goals can be achieved optimally when employees have adequate competence  in understanding their roles and responsibilities. Therefore, the agenda for developing employee capacity  is also an important mission in increasing employee competence, one of which is through training activities.  Computer training for Directorate General of Taxation employees is intended so that the absorption of  Information Technology can contribute to increasing productivity and the quality of employee performance.  Based on the operational data processing needs of their current jobs, the training was focused on using  Microsoft Office programs, especially Microsoft Excel. It is hoped that through the Microsoft Office  training program, especially the basic level of Microsoft Excel, for employees of the Directorate General  of Taxes, Regional Office II, South Jakarta, can be a useful contribution to increasing the ability of  employees so that their productivity and quality of performance increase. AbstrakPencapaian tujuan perusahaan mampu dicapai secara optimal manakala para pegawai memiliki  kompetensi yang memadai dalam memahami peran dan tanggungjawabnya. Oleh sebab itu, agenda  pengembangan kapasitas pegawai juga merupakan misi penting dalam meningkatkan kompetensi pegawai  salah satunya dengan kegiatan pelatihan. Pelatihan komputer bagi para pegawai Direktorat Jendral Pajak  dimaksudkan agar penyerapan Teknologi Informasi dapat menjadi kontribusi peningkatan produktivitas  dan kualitas kinerja para pegawai. Berdasarkan kebutuhan pengolahan data operasional pekerjaan  mereka saat ini, maka pelatihan dipusatkan pada penggunaan program Microsoft Office terutama  Microsoft Excel. Diharapkan melalui program pelatihan Microsoft Office terutama Microsoft Excel tingkat  dasar bagi para pegawai Direktorat Jendral Pajak Kanwil II Jakarta Selatan dapat menjadi kontribusi  yang bermanfaat untuk peningkatan kemampuan para pegawai agar produktifitas dan kualitan kinerja  mereka meningkat.